PERMASALAHAN ANAK DALAM ISLAM - Abdul Wahab Syakhrani; Ahmad Fahrul Islam AS, Laila, Nournaina (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Children are biological descendants (flesh and blood) of their parents or are not biological descendants, but because there are other factors that cause the relationship between children and their parents. Adoption, like the traditional practice in the Jahiliyah era, which gave adopted children the same status as biological children, is not permitted (forbidden) and is not recognized by Islam. The relationship between adopted children and their adoptive parents and family remains as before adoption, which does not affect inheritance and inheritance, whether the adopted child is taken from within one's own relatives, as in Java, where most of one's own nephews are taken as adopted children, or taken outside the circle of relatives. Likewise, adopted children should not have the same status as biological children, in all matters, such as guardianship, inheritance and other obligations. Islam even allows someone to marry their adopted child. Likewise, biological children and adopted children. Nursing children may become mahram (prayers are not invalidated). For example, say a woman takes a man's adopted child, the woman is adopted by him, so the woman's nurse child becomes the woman's mahram, from a legal perspective, it is haram to marry the woman's biological daughter, and also the woman. If a woman takes an adopted daughter, the woman breastfeeds it, it is unlawful for the woman's suckling child to marry the woman's biological male children, and it is unlawful to marry the woman's husband. But with certain conditions.